Development and validation of an NFC-based laboratory inventory management system for the UP College of Pharmacy Industrial Pharmacy Laboratory - Borcelis, Gia Ela B.
Manual tracking of inventory in the University of the Philippines College of Pharmacy (UPCP) Industrial Pharmacy (IP) Laboratory faces several limitations, such as unmonitored real-time availability of reagents, issues involving supply and re-ordering, and failure to update item deficiencies, leading to laboratory inefficiencies. The absence of a proper documentation system leads to untracked reagent usage, often causing shortages during laboratory classes. As the central dispensary unit for reagents in UPCP, the IP Laboratory requires an accurate and real-time system that monitors reagent usage and transactions. Near Field Communication (NFC) Technology is a rising technological development that offers this advantage as it is utilized in contactless transactions and inventory management. This study aims to develop and validate an NFC-based laboratory inventory management tool for the UPCP IP Laboratory that can automate and digitize laboratory transactions via Google Sheets. This has features such as a search functionality for reagent availability and generation of reagent inventory cards that compile the borrowing history and subject consumption of reagents. The spreadsheet was populated with relevant sheets, including the inventory database, student database, and faculty database. An Apps Script code was created to automate the borrowing and returning processes, which were logged in a designated sheet. Reports involving the top 15 fast-moving reagents, reagent consumption per subject, low-stock items, expired items, and items with signs of contamination were also generated in a separate sheet. These reports can then be sent to the faculty and laboratory managers to support decisions for reagent replenishments. Implementing an online inventory management system can streamline transactions, enhance accuracy, while also helping the UPCP laboratories comply with Good Documentation Practice, Good Manufacturing Practice, and Good Dispensing Practice. In conclusion, the NFC-based Laboratory Inventory Management System was developed to automate and digitize inventory transactions in the UPCP IP Laboratory. It was confirmed to generate accurate results and reports through validation testing, which also ensures the reliability, usability, and functionality of the inventory system.